2023
DOI: 10.1038/s41372-023-01748-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental consequences of short apneas and periodic breathing in preterm infants

Alicia K. Yee,
Leon S. Siriwardhana,
Gillian M. Nixson
et al.

Abstract: Objective We investigated the relationship between respiratory events experienced before and after hospital discharge and developmental outcomes at 6 months corrected age (CA). Study design Preterm infants born between 28–32 weeks gestational age (GA) were studied at 32–36 weeks postmenstrual age (PMA), 36–40 weeks PMA, 3- and 6-months CA. Percentage total sleep time (%TST) with respiratory events (isolated apneas, sequential apneas and periodic breathing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Several studies have shown associations between reduced cerebral oxygenation during the neonatal period and neurodevelopmental outcomes 26–29 however not all have shown this link, probably because of differences in the level and duration of hypoxia 30 . In this same group of infants, we have shown that the time spent with central apnoeas, specifically with periodic breathing at 36–40 PMA, was negatively associated with language and motor scores at 6 months CA 13 …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Several studies have shown associations between reduced cerebral oxygenation during the neonatal period and neurodevelopmental outcomes 26–29 however not all have shown this link, probably because of differences in the level and duration of hypoxia 30 . In this same group of infants, we have shown that the time spent with central apnoeas, specifically with periodic breathing at 36–40 PMA, was negatively associated with language and motor scores at 6 months CA 13 …”
Section: Discussionmentioning
confidence: 56%
“…Parents gave written informed consent before the first study. We have previously reported the risk factors for periodic breathing, 12 measurements of cerebral oxygenation during periods of periodic breathing 11 and the relationship between time spent with apnoea and developmental outcomes 13 in this cohort of infants.…”
Section: Methodsmentioning
confidence: 98%
“…In China, the rate of preterm birth is also on the rise ( 4 ). Each year, approximately 1.1 million newborns die from preterm birth ( 5 ) and its related complications, including respiratory distress syndrome ( 6 ), apnea ( 7 ), metabolic disorders, anemia, and feeding intolerance ( 8 ). Even infants who survive may suffer from long-term sequelae such as growth retardation, chronic lung disease, cerebral palsy, and more, posing a significant economic burden on families and society ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…These events, characterized by breathing interruptions and associated bradycardia, can result in hypoxemia and cerebral hypoperfusion, posing immediate threats to the infant's well-being [8]. Furthermore, the long-term consequences extend to potential neurodevelopmental disorders, which are well documented in preterm infants [8,9]. Bradycardia contributes substantially to morbidity and mortality in this vulnerable population [10].…”
Section: Introductionmentioning
confidence: 99%